Ethnography of a Consultation that Doesn’t Take Place - Langlois, Marie-Dominik (2025)
This article sets out to reveal the conditions of research production in a «social minefield» (Albera, 2001; Rodríguez-Garavito, 2011) characterized by the uncertainty of its object and the dynamics of social interactions generated by the struggles around free, prior, and informed consent (FPIC). Reflexive analysis of the «ethnographic concerns» (Fassin, 2008) contributed to the construction and clarification of the research object. Based on an ethnographic survey of the occupations of a mining resistance movement, the text analyzes the uncertainties surrounding the exhaustion of the consultation process of the Xinka people on the Escobal mine in the Southeast region of Guatemala in Central America, in order to highlight how the consultation can be interpreted as an object of resistance by the subjects of resistance in a mining context, due to its slow process.